Pengaruh Brand Image dan E-Service Quality Terhadap Kepuasan Pelanggan Marketplace Lazada di Kota Bandung - Ferdiansyah Pramudya; Ridho Riadi Akbar (eCo-Buss, 2024)
The speed at which technology is developing, particularly in Indonesia, is causing profound changes in people, and these changes undoubtedly have a significant impact on societal values. The Internet is one of the technological advancements that society uses on a daily basis. This study set out to ascertain how customer satisfaction for Bandung City Lazada Marketplace customers was impacted by brand image and e-service quality. With approaches to verification and description, the research methodology is quantitative. The process of gathering data involved giving questionnaires to one hundred respondents. The Nonprobability Sampling with Purposive Sampling approach, which selects samples based on predetermined criteria, is the sampling methodology employed in this investigation. The study's sample consisted of Bandung City-based Lazada users who were between the ages of 17 and 30 and had completed purchases. The validity, reliability, hypothesis, classical assumption, t, and f tests are all used in this study. The data indicates that customer happiness is significantly impacted by brand image and e-service quality. The results are statistically significant, as indicated by a t-value of 2.671, which is located above the t-critical table's value of 1,660. In addition, the significance level of 0.009 is higher than the conventional batas mean of 0.05. Due to this, the second hypothesis (H2) is confirmed, indicating that the quality of the services has a negative impact on the consumer's behavior in the online study conducted in the city of Bandung.